Kogrog: The Collective Process of Painting in a Kaingang Basket - Souza, Sheilla P. Dias de; Neri, Maria Vitória; Glicério, Sanda Kokrog Ninvaia; Jesus, Raquel Rodrigues de (Farol, 2022)
This text was written from methodologies associated with decolonialism in the arts,the concept of epistemicide, research in arts and autoethnography, with which we sought topromote a collective creation among students of Visual Arts and Kaingang professors. It is ananalysis of a painting collectively made on a Kaingang basket, with the aim of sharingdifferent experiences and promoting greater knowledge about Kaingang culture withouttaking away the indigenous role.
Keywords: Artistic co-creation; Kaingang Culture; Basketry; Indigenous culture; Painting